Strategi Komunikasi Pemasaran Pada Kaze Hairstudio Karawang - Nuraghani, Arya; Ramdhani, Muhammad; Oxcygentri, Oky (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research is entitled Marketing Communication Strategy at Kaze Hairstudio Karawang. The purpose of this study was to determine the Marketing Communication Strategy of Kaze Hairstudio Karawang in increasing sales. This research uses the 4P Marketing Mix theory. The object of this research is Kaze Hairstudio which is located on Jl. HS. Ronggowauyo No. 88, East Teluk Jambe, Karawang Regency. Data collection techniques through observation, interviews and documentation. The results of this study can be concluded that the most effective marketing communication carried out by Kaze Hairstudio is promotion, namely providing discounts and vouchers that aim to attract customers. In addition to the most effective promotion, namely advertising (advertising) and also endorsement have an effect on Kaze Hairstudio's marketing communication strategy, namely by publishing content on Instagram social media.